Music in Obstetrics: An Intervention Option to Reduce Tension, Pain and Stress - Wulff, Verena; Hepp, Philip; Fehm, Tanja; Schaal, Nora K. (Geburtshilfe und Frauenheilkunde, 2017)
In recent years, the effect of music interventions and music therapy has experienced increased attention in the literature. It has been shown that music has positive effects on cognitive and physical performance, such as concentration and endurance, as well as on psychological parameters, such as anxiety and relaxation. Studies within the context of medicine in particular are increasingly indicating that music may be used as an intervention for relief against anxiety, stress and pain. Music is therefore seen in actual practice as a supplement to conventional pharmacological and non-pharmacological forms of treatment – and the trend is rising. Studies involving music interventions in the field of obstetrics have shown, amongst other things, that music improves the ability to relax during pregnancy and can reduce anxiety. It was also discovered that during childbirth music interventions resulted in a reduction of pain and stress. Music also has the effect of reducing stress, pain and anxiety in expectant mothers during deliveries by caesarean section. This review intends to provide an overview of the literature on music interventions in the field of obstetrics and to give a resume on the current state of research around the topic of music in relation to pregnancy, spontaneous deliveries and caesarean sections. Furthermore, the relevance of music for everyday obstetrics will be illustrated.In den letzten Jahren wurde die Wirkung von Musikinterventionen und Musiktherapie in der Literatur vermehrt dargestellt. Dabei konnten positive Effekte der Musik auf kognitive und körperliche Leistungen, wie Konzentration oder Ausdauer, sowie auf psychologische Parameter, wie Angst oder Entspannung, gezeigt werden. Vor allem im medizinischen Kontext weisen Studien zunehmend darauf hin, dass Musik als angst-, stress- und schmerzlindernde Intervention eingesetzt werden kann. Daher wird Musik in der Praxis mit steigender Tendenz als Zusatz zu herkömmlichen pharmakologischen und nicht pharmakologischen Behandlungen gesehen. Bei Untersuchungen von Musikinterventionen im Bereich der Geburtshilfe zeigte sich unter anderem, dass Musik während der Schwangerschaft die Entspannungsfähigkeit verbessert sowie Ängste vermindern kann. Auch während der Geburt konnte festgestellt werden, dass Musikinterventionen eine Schmerz- und Stressreduktion zur Folge haben. Bei Geburten durch eine Sectio caesarea wirkt sich Musik ebenfalls stress-, schmerz- und angstreduzierend auf die werdenden Mütter aus. Dieses Review soll einen Überblick über die Literatur der musiktherapeutischen Interventionen im Bereich der Geburtshilfe geben und den aktuellen Forschungsstand zum Thema Musik in Bezug auf Schwangerschaft, spontane Geburten sowie Sectio caesarea zusammenfassen. Des Weiteren wird die Relevanz von Musik für den geburtshilflichen Alltag aufgezeigt.
Keywords: music; pregnancy; spontaneous delivery; caesarean section; relaxation